2012
DOI: 10.1177/0893318912443776
|View full text |Cite
|
Sign up to set email alerts
|

“What Are You Going to Do With That Major?” Colloquial Speech and the Meanings of Work and Education

Abstract: This article explores the function of the ubiquitous question, "What are you going to do with that major?," in advancing particular meanings of work, higher education, and the work-higher education relationship. Analyzing 110 student descriptions of encounters with the question suggests that the colloquialism powerfully shapes student interpretations of work and education, cementing vocational understandings of higher education and perpetuating a linear view of careers. Such interpretations pressure students t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 39 publications
2
33
0
2
Order By: Relevance
“…To begin, the current study identified money as the top characteristic of a real job, a finding similar to previous research (Clair, 1996;Lair & Wieland, 2012). However, students in this study did not expect a real job to provide a "six figure salary," as was reported in Clair's (1996, p. 257) findings.…”
Section: Millennials Get a "Real Job" 13supporting
confidence: 86%
See 2 more Smart Citations
“…To begin, the current study identified money as the top characteristic of a real job, a finding similar to previous research (Clair, 1996;Lair & Wieland, 2012). However, students in this study did not expect a real job to provide a "six figure salary," as was reported in Clair's (1996, p. 257) findings.…”
Section: Millennials Get a "Real Job" 13supporting
confidence: 86%
“…To answer the research questions of this study, we utilized a purposive sample of students (juniors and seniors) enrolled in three upper division communication courses at a mid-sized Midwestern university. College students' understandings of the real job colloquialism are removed from a specific organizational context (Kramer & Miller, 1999) and role-specific contexts (Kramer, 2010;Lair & Wieland, 2012). Further, because of their impending transition between pre-and post-college employment, the term has high salience for the participants (Clair, 1996).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vocational anticipatory socialization includes messages people receive about specific roles (e.g., Kramer, 2010;Myers, 1994), work in general (e.g., Clair, 1996;Lair & Wieland, 2012), and careers-an "overarching structure that brings together jobs, work, and occupations" (Buzzanell, Berkelaar, & Kisselburgh, 2012, p. 2).…”
Section: Vocational Anticipatory Socialization Vocational Anticipatomentioning
confidence: 99%
“…No Brasil, essa "reprodução cega" da classe, segundoSouza (2010), tem seu ápice na classe média e na dita "nova classe média", por ocorrer de forma extremamente íntima, emocional, através do exemplo.O interesse acadêmico pelos jovens, de acordo comGonçalves (2005), desponta de tempos em tempos. Inclusive, atualmente, é notório que este segmento etário se destaca como um grupo que concentra grande atenção por parte de pesquisadores, principalmente entre aqueles que se dedicam a estudar o sentido do trabalho(RUIZ et al 2008;FERRARI et al 2009;RIZZO;CHAMON, 2010;OLIVEIRA, 2011;WRAY-LAKE et al 2011;CAVAZOTTE, LEMOS, VIANA, 2012;LAIR;WIELAND, 2012, TEIXEIRA et al 2014; O'CONNOR; RAILE, quando comumente tem-se o início da vida profissionalpossibilitaria a identificação de tendências sobre como o mercado de trabalho tenderia a se desenvolver num futuro próximo(WRAY-LAKE et al 2011).De todo o corpo teórico produzido, todavia, chama atenção uma questão referente à diversidade social dos jovens contemplados por essas pesquisas (ROCHA-DE-OLIVEIRA, PICCININI, SILVEIRA, 2010). Lemos, Mello e Guimarães (2014) explicam que em sua maioria, os estudos partem de uma perspectiva ocidental e consideram jovens pertencentes às classes sociais mais abastadas.…”
unclassified